ANALISIS MANAJEMEN BISNIS SYARIAH TERHADAP PROGRAM PEMERINTAH KABUPATEN BOGOR DALAM MELINDUNGI UMKM AKIBAT MASA PANDEMI COVID-19 - Vivih Sofianti; Tubagus Rifqy Thantawi; Mohammad Kharis Mubarok (Jurnal Penelitian Manajemen Bisnis Syariah: Program Studi Manajemen Bisnis Syariah, 2021)
Abstract This research is in the background due to the Covid-19 pandemic which has spread throughout the world, including Indonesia. As a result of the Covid-19 outbreak, the Indonesian Government issued a policy of Locdown (area quarantine) and PSBB (Large-Scale Social Restrictions) Bogor Regency, one of the regions that followed the policies of the Government. Because of that the community should remain silent at home. The result is a decrease in the income of MSMEs. Data on SMEs affected by Covid-19 were 1,120 SMEs in Bogor Regency. Therefore, the Bogor Regency Government through the Bogor Regency Trade and Industry Service and the Bogor Regency Small and Medium Business Cooperative Office need to issue a program to protect MSMEs during the Covid-19 pandemic. Data collection was carried out through interviews, observation and documentation with the Bogor Regency Trade and Industry Office and the Bogor Regency Small and Medium Enterprises Cooperative Office. The efforts of DISPERDAGIN and the Office of Cooperatives and Small and Medium Enterprises (UKM) by way of direct surveys, and data on MSMEs affected by Covid-19. From this data, the Agency makes a program in accordance with the complaints of MSMEs. The program plan will be implemented in 2021 because the Bogor Regency Government program has been ratified before the pandemic begins, therefore technically the program will be implemented starting in 2021. Keywords: Bogor Regency Government Programs, MSMEs, Covid-19, Islamic Business Management Analysis